DIGITAL TECHNOLOGY – FLIPBOOK MAKER AS THE LEARNING MEDIA TO INCREASE ENGLISH READING SKILL: Teknologi Digital – Flipbook Maker Sebagai Media Pembelajaran Untuk Meningkatkan Keterampilan Membaca Bahasa Inggris - Litta, Lista; Ayu Annisa Akbar; Christine Andu; Ratih Puspita Siwi (TEKNOS: Jurnal Pendidikan dan Teknologi, 2023)
The globalization of Digital technology has impacted all facets of life including education, Therefore, using digital technology in teaching is very important.This research aims to investigate whether or not using digital technology – flipbook maker as a media effective to increase English reading skill and whether or not the students are interested in using digital technology – flipbook maker as a media to increase English reading skill. This research employed Research and development (R&D ) method. The population of this research was the tenth grade students of Frater Senior High School Makassar academic year 2023/2024. This research used cluster random sampling. The sample consisted of 30 students. The data was collected by using a reading test and quisionare. The findings showed that students’ result of the posttest was improved than the students’ result of the pretest by the mean score of 54,83 > 82,17. Then, the mean score of the student’s interest was categorized as strongly interested classification by mean score 88,17.